The Role of Urine Liver Fatty Acid Binding Protein in Early Detection of Acute Kidney Injury in Septic Patient - Adrian Hartomuljono; Andi Salahuddin; Hisbullah Amin; Syafruddin Gaus; Haizah Nurdin; Faisal Muchtar; Evan Kristiono (Egyptian Journal of Critical Care Medicine)
Abstract Introduction Acute kidney injury (AKI) occurred more than 20% in patients with sepsis and 50% in septic shock. Urine liver-fatty acid binding protein (uL-FABP) has been proposed to be a useful biomarker for early detection of AKI. This biomarker increases up to 20 hours before an increase in serum creatinine. Objective Assesing uL-FABP as an early biomarker of the occurrence of AKI in septic patient. Methods The design used is a diagnostic test. Sampling in cross-sectional consecutive sampling in ICU Dr. Wahidin Sudirohusodo Makassar General Hospital and satellite hospital covering 28 sepsis patients and 26 septic shock patients. The qSOFA criteria was used to define sepsis. AKI is defined as an increase in serum creatinine based on Risk, Injury, Failure, Loss, End-stage Kidney Disease (RIFLE) criteria. uL-FABP levels were measured by enzyme linked immunoassay. Results There were significant differences in the levels of uL-FABP and serum creatinine based on the severity of sepsis (P < .05). There was a significant difference between the severity of AKI according to the RIFLE criteria and the severity of sepsis (P < .05). There is a correlation between uL-FABP and RIFLE criteria (P < .05). The sensitivity value of uL-FABP was 95.2% and the specificity was 54.5%, positive predictive value was 57.1% and negative predictive value was 94.7% and area under the curve was 0.92. Discussion uL-FABP may be a promising for early detection of AKI. Its potential value needs to be validated in large studies and comparisons with other AKI biomarkers are required to continue the development of this promising biomarker.